Significance of knowledge management practices effecting supply chain performance - Muhammad Khyzer Bin Dost; Chaudhry Abdul Rehman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
The purpose of this research is to examine how knowledge management practices (KMP) influence supply chain performance (SCP) with mediating role of supply chain coordination (SCC). This research is conducted in Central Punjab Pakistan, which had not been investigated before. This research comprises three stages of statistical analysis where phase one is descriptive statistics and reliability, phase two is factor analysis (KMO and Bartlett's test, Eigen values and total variance) and third phase is path analysis that was used to analyze the data. Based on literature, a theoretical framework was developed consisting of four KMP; knowledge storage, knowledge sharing, knowledge creation and knowledge application and SCP is evaluated by efficiency, flexibility, responsiveness and quality, and SCC is measured by information sharing, quality of information and bullwhip effects. Structural equation modeling was employed using a sample of 19 milk processing companies of central Punjab. The tremendous results of this study have shown that the implementation of KMP interact with SCC to influence supply chain performance (SCP). The empirical results also show that KMP have significant impact on SCP which is positively mediated by SCC. The relationship between knowledge application and supply chain performance is not significant. Since the sample of this research is small and taken only from milk processing companies, it would be important to consider other companies with large sample from wider range of companies. In addition, other variables can be considering in proposed model to strengthen and improve our analyses and generalizable results. Through this study, a good understanding of relationship of KMP and SCP and mediating role of SCC can be gained. Further, that is important gap in supply chain and knowledge management literature that there is no empirical study specifically examine mediating effect of supply chain coordination affecting the relationship of SCP and KMP.
Keywords: 330; supply chain performance (SCP); knowledge creation (KC); knowledge management practices (KMP); knowledge sharing (KSH); knowledge storage (KST); knowledge application (KA); supply chain coordination (SCC); dairy industry